Preparation method of environment-friendly heat-conducting plastic particles
By pretreating aluminum trioxide and aluminum and modifying thermal fillers with γ-aminopropyltriethoxysilane and tetramethoxysilane, the problem of uneven dispersion of fillers in thermal plastics is solved, which significantly improves the Thermal conductivity and mechanical properties also reduce production costs.
Patent Information
- Application Number
- CN202411833421.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-02-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
After the existing thermally conductive plastics are filled with high thermal conductivity inorganic fillers, the compatibility between the fillers and the polymer matrix is poor, resulting in uneven dispersion of the fillers and reducing the overall thermal conductivity and mechanical properties of the material.
Improve the fusion of filler and polymer matrix by using economical and environmentally friendly aluminum trioxide and aluminum for surface pretreatment, combined with gamma-aminopropyltriethoxysilane and tetramethoxysilane as modification reagents for thermally conductive fillers, the fusion of fillers and polymer matrix is improved. , improve thermal conductivity.
It significantly improves the thermal conductivity and mechanical properties of composite materials, reduces production costs, and has antibacterial, mildew and corrosion resistance, extending the service life of the product.
Smart Images

Figure BDA0005186096180000141 
Figure BDA0005186096180000151
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of thermal conductive plastics, and in particular to a method for preparing environmentally friendly thermal conductive plastic particles. Background Art
[0002] Thermally conductive plastics are widely used in many fields such as electrical and electronic, automotive, aerospace, healthcare, and industry. Thermally conductive plastics mainly include synthetic and filled types. Among them, synthetic thermally conductive plastics are achieved by introducing structural units with high thermal conductivity into the polymer molecular chain, and have the advantages of high thermal conductivity and uniform and stable performance. However, synthetic thermally conductive plastics usually involve complex chemical synthesis processes, which are difficult to process and have high synthesis costs. Filled thermally conductive plastics are made by adding highly thermally conductive inorganic fillers (such as metal powders, carbon-based materials, ceramic particles, etc.) to the polymer matrix to fill the polymer to improve thermal conductivity. Compared with synthetic thermally conductive plastics, filled thermally conductive plastics are relatively low in cost, and the thermal conductivity of the material can be flexibly controlled by adjusting the type, particle size and amount of filler added. However, although the thermal conductivity of the material can be significantly improved by adding inorganic fillers, the compatibility of inorganic fillers with the polymer matrix is poor, resulting in uneven dispersion of the fillers in the matrix and easy agglomeration. This not only reduces the overall mechanical properties and processing properties of the plastic particles, but also causes the formation of areas with greater thermal resistance inside the plastic particle product, thereby reducing the overall thermal conductivity.
[0003] With the continuous advancement of materials science and engineering technology, people have higher and higher functional requirements for thermal conductive plastics. How to obtain highly thermal conductive plastic particles with high filler filling, ensure the mechanical properties and processing properties of plastic particles, and avoid brittle materials has become an important development direction of the thermal conductive plastic industry. While pursuing high performance, people's awareness of environmental protection and antibacterial is increasing. This trend not only promotes the overall improvement of product quality, but also significantly extends the service life of products, reduces resource consumption and environmental pollution, promotes technological innovation in the entire industry, and promotes sustainable development of the industry. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides a method for preparing environmentally friendly thermally conductive plastic particles, which is filled with economical and environmentally friendly aluminum oxide and aluminum, and subjected to surface pretreatment to improve the material refinement level, thereby promoting full fusion of the polymer matrix and the thermally conductive filler, thereby improving the thermal conductivity of the thermally conductive polymer material, greatly reducing the production cost of the product while protecting the environment, effectively improving thermal conductivity and having both antibacterial, anti-mildew and anti-corrosion properties.
[0005] The technical solution adopted by the present invention is:
[0006] A method for preparing environmentally friendly thermally conductive plastic particles comprises the following steps:
[0007] S1. Material preparation: weigh 40-60 parts of polyethylene, 20-30 parts of polyphenylene sulfide, 1-3 parts of compatibilizer, 50-65 parts of thermal conductive filler, 3-5 parts of composite antibacterial agent, and 5-10 parts of processing aid, by weight, and set aside;
[0008] S2, material mixing: adding polyethylene, polyphenylene sulfide, compatibilizer, and thermal conductive filler into a high-speed mixer, stirring and mixing them thoroughly to obtain a first mixture; then adding a composite antibacterial agent and a processing aid to the first mixture, stirring and mixing them thoroughly again, to obtain a second mixture for standby use;
[0009] S3, molding preparation: the second mixture prepared in step S2 is extruded by a twin-screw extruder and granulated to obtain thermally conductive plastic particles.
[0010] Preferably, in step S1, the polyethylene is low-density polyethylene, and the mass ratio of polyethylene to polyphenylene sulfide is 2-2.5:1, and the compatibilizer is maleic anhydride grafted polyethylene.
[0011] Preferably, calculated by weight, the thermally conductive filler in step S1 is prepared by the following method:
[0012] (1) Pretreatment of aluminum oxide and aluminum: Aluminum oxide and aluminum are mixed and ground in a mass ratio of 8-12:12-20, and sieved to obtain a 200-300 mesh mixture;
[0013] (2) stirring and dispersing a silane coupling agent, anhydrous ethanol and 22-30 wt % ammonia water in a mass ratio of 0.1-0.5:4-8:4-10 to obtain a mixed solution;
[0014] (3) Add the mixed material to the mixed liquid, stir and disperse, then add acetic acid, adjust the pH to 5-6, ultrasonically disperse, and dry to constant weight to obtain the desired thermal conductive filler.
[0015] Preferably, the silane coupling agent is γ-aminopropyltriethoxysilane and tetramethoxysilane in a mass ratio of 1-2:2-3.
[0016] Preferably, the composite antibacterial agent in step S1 is prepared by the following method:
[0017] (1) mixing graphene oxide dispersion, chitosan quaternary ammonium salt solution and d-limonene in a mass ratio of 3-5:2-3:0.03-0.04, and ultrasonically dispersing to obtain a mixed solution;
[0018] (2) After ultrasonic dispersion for 5 minutes, epichlorohydrin is added at a concentration of 3-8% of the total mass of the mixed solution, and ultrasonic dispersion is continued for 10 minutes to form a complex;
[0019] (3) Drying the above-mentioned composite to a constant weight to obtain a composite antibacterial agent.
[0020] Preferably, in step S2, the first mixture is prepared by stirring in a high-speed mixer at a rotation speed of 1500-2000 rpm for 15-20 min, and the second mixture is prepared by stirring in a high-speed mixer at a rotation speed of 4500-6500 rpm for 30-40 min.
[0021] Preferably, in step S3, the temperature of the twin-screw extruder is 280-300° C., the aspect ratio of the screw is 15-20:1, and the rotation speed is 400-500 rpm.
[0022] Preferably, the processing aid in step S1 is one or more of a flame retardant, a lubricant, an antioxidant, and a toughening agent.
[0023] Beneficial effects of the present invention:
[0024] The present invention combines an economical and environmentally friendly matrix material with a thermally conductive filler, pre-treats and modifies the thermally conductive filler, and uses γ-aminopropyltriethoxysilane and tetramethoxysilane as modifying agents for the thermally conductive filler. Due to the complementarity of the functional groups of the two silane coupling agents, the interface bonding between the filler and the polymer is more firmly established, forming a stronger interface layer. The enhanced interface bonding helps to reduce the interface thermal resistance of the system, thereby further improving the thermal conductivity of the composite material, and helps to optimize the distribution state of the filler, so that it is more evenly and densely distributed in the polymer matrix, thereby improving the overall thermal conductivity of the composite material. The composite antibacterial agent is prepared by adding graphene oxide dispersion, chitosan quaternary ammonium salt solution and d-limonene for mixed cross-linking. The physical destruction and oxidative stress of graphene oxide dispersion, the positive charge and broad-spectrum antibacterial property of chitosan quaternary ammonium salt solution, the natural antibacterial property of D-limonene and the synergistic effect among the three are utilized to enhance the material's ability to resist microbial invasion, expand the material's scope of use, extend the product's service life, reduce resource consumption and environmental pollution, and promote technological innovation in the entire industry. DETAILED DESCRIPTION
[0025] In order to make the embodiments of the present invention easier to understand, the present invention will be described in detail below with reference to specific examples. These examples are only for illustration and are not intended to limit the scope of application of the present invention.
[0026] The present invention provides a method for preparing environmentally friendly thermally conductive plastic particles, which adopts the following technical scheme:
[0027] Example 1
[0028] The present invention provides a method for preparing environmentally friendly thermally conductive plastic particles, which specifically comprises the following steps:
[0029] S1. Material preparation: weigh 40 parts of low-density polyethylene, 20 parts of polyphenylene sulfide, 1 part of maleic anhydride grafted polyethylene, 50 parts of thermal conductive filler, 3 parts of composite antibacterial agent, and 5 parts of industrial magnesium hydroxide by weight, and set aside;
[0030] S2, material mixing: low-density polyethylene, polyphenylene sulfide, maleic anhydride grafted polyethylene, and thermal conductive filler are added to a high-speed mixer with a rotation speed of 1500 rpm, stirred for 15 minutes to fully mix, and a first mixture is obtained; then, the composite antibacterial agent and industrial magnesium hydroxide are added to the first mixture, and stirred again at a rotation speed of 4500 rpm for 30 minutes, and the mixture is fully stirred and mixed to obtain a second mixture for standby use;
[0031] S3, molding preparation: the second mixture prepared in step S2 is extruded by a twin-screw extruder with a screw length-to-diameter ratio of 15:1, a rotation speed of 400 rpm, and a temperature of 280° C., and granulated to prepare thermally conductive plastic particles.
[0032] In the present invention, the thermal conductive filler is prepared by the following method:
[0033] (1) Pretreatment of aluminum oxide and aluminum: Aluminum oxide and aluminum are mixed and ground in a mass ratio of 8:12, and sieved to obtain a 200-mesh mixed material;
[0034] (2) stirring and dispersing a silane coupling agent, anhydrous ethanol and 22 wt% ammonia water in a mass ratio of 0.1:4:4 to obtain a mixed solution, wherein the silane coupling agent is γ-aminopropyltriethoxysilane and tetramethoxysilane in a mass ratio of 1:2;
[0035] (3) Add the mixed material to the mixed liquid, stir and disperse at room temperature for 15 minutes, then add acetic acid to adjust the pH to 5, raise the temperature to 45°C, control the ultrasonic power to 100W, the ultrasonic frequency to 60kHz, ultrasonically disperse for 15 minutes, and dry to constant weight to obtain the desired thermal conductive filler.
[0036] In the present invention, the composite antibacterial agent is prepared by the following method:
[0037] (1) A 2 mg / mL graphene oxide dispersion (active ingredient content 96%), a 0.05 mg / mL chitosan quaternary ammonium salt solution (degree of substitution 90%) and d-limonene were mixed in a mass ratio of 3:2:0.03, and the ultrasonic power was controlled to 90 W and the ultrasonic frequency to 60 kHz, and the mixed solution was obtained by ultrasonic dispersion for 15 min;
[0038] (2) After ultrasonic dispersion for 5 min at an ultrasonic power of 90 W and an ultrasonic frequency of 60 kHz, epichlorohydrin (3% by weight of the total mass of the mixed solution) was added and ultrasonic dispersion was continued for 10 min to form a complex;
[0039] (3) Drying the above-mentioned composite to a constant weight to obtain a composite antibacterial agent.
[0040] Example 2
[0041] The present invention provides a method for preparing environmentally friendly thermally conductive plastic particles, which specifically comprises the following steps:
[0042] S1. Material preparation: weigh 50 parts of low-density polyethylene, 25 parts of polyphenylene sulfide, 2 parts of maleic anhydride grafted polyethylene, 60 parts of thermal conductive filler, 4 parts of composite antibacterial agent, and 8 parts of polyethylene wax by weight, and set aside;
[0043] S2, material mixing: low-density polyethylene, polyphenylene sulfide, maleic anhydride grafted polyethylene, and thermal conductive filler are added to a high-speed mixer with a rotation speed of 1800 rpm, and the mixture is rotated for 18 minutes to be fully stirred and mixed to obtain a first mixture; then, the composite antibacterial agent and polyethylene wax are added to the first mixture, and the mixture is rotated again at a rotation speed of 5500 rpm for 35 minutes to be fully stirred and mixed to obtain a second mixture for standby use;
[0044] S3, molding preparation: the second mixture prepared in step S2 is extruded by a twin-screw extruder with a screw length-to-diameter ratio of 18:1, a rotation speed of 450 rpm, and a temperature of 290° C., and granulated to prepare thermally conductive plastic particles.
[0045] In the present invention, the thermal conductive filler is prepared by the following method:
[0046] (1) Pretreatment of aluminum oxide and aluminum: Aluminum oxide and aluminum are mixed and ground in a mass ratio of 10:15, and sieved to obtain a 250-mesh mixed material;
[0047] (2) stirring and dispersing a silane coupling agent, anhydrous ethanol and 22 wt % ammonia water in a mass ratio of 0.3:6:7 to obtain a mixed solution, wherein the silane coupling agent is γ-aminopropyltriethoxysilane and tetramethoxysilane in a mass ratio of 1.5:2.5;
[0048] (3) Add the mixed material to the mixed liquid, stir and disperse at room temperature for 15 minutes, then add acetic acid to adjust the pH to 5.5, raise the temperature to 45°C, control the ultrasonic power to 100W, the ultrasonic frequency to 60kHz, and ultrasonically disperse for 15 minutes, then dry to constant weight to obtain the desired thermal conductive filler.
[0049] In the present invention, the composite antibacterial agent is prepared by the following method:
[0050] (1) A 2 mg / mL graphene oxide dispersion (active ingredient content 96%), a 0.05 mg / mL chitosan quaternary ammonium salt solution (degree of substitution 90%) and d-limonene were mixed in a mass ratio of 4:2.5:0.035, and the ultrasonic power was controlled to 90 W and the ultrasonic frequency to 60 kHz for 15 min to obtain a mixed solution;
[0051] (2) After ultrasonic dispersion for 5 min at an ultrasonic power of 90 W and an ultrasonic frequency of 60 kHz, epichlorohydrin (5% by weight of the total mass of the mixed solution) was added and ultrasonic dispersion was continued for 10 min to form a complex;
[0052] (3) Dry the above-mentioned composite to constant weight to obtain a composite antibacterial agent.
[0053] Example 3
[0054] The present invention provides a method for preparing environmentally friendly thermally conductive plastic particles, which specifically comprises the following steps:
[0055] S1. Material preparation: weigh 60 parts of low-density polyethylene, 30 parts of polyphenylene sulfide, 3 parts of maleic anhydride grafted polyethylene, 65 parts of thermal conductive filler, 5 parts of composite antibacterial agent, and 10 parts of styrene-isoprene-styrene by weight, and set aside;
[0056] S2, material mixing: low-density polyethylene, polyphenylene sulfide, maleic anhydride grafted polyethylene, and thermal conductive filler are added to a high-speed mixer with a rotation speed of 2000 rpm, and the mixture is rotated for 20 minutes and stirred to obtain a first mixture; then, the composite antibacterial agent and styrene-isoprene-styrene are added to the first mixture, and the mixture is rotated again at a rotation speed of 6500 rpm for 40 minutes, and stirred to obtain a second mixture for standby use;
[0057] S3, molding preparation: the second mixture prepared in step S2 is extruded by a twin-screw extruder with a screw length-to-diameter ratio of 20:1, a rotation speed of 500 rpm, and a temperature of 300° C., and granulated to prepare thermally conductive plastic particles.
[0058] In the present invention, the thermal conductive filler is prepared by the following method:
[0059] (1) Pretreatment of aluminum oxide and aluminum: Aluminum oxide and aluminum are mixed and ground in a mass ratio of 12:20, and sieved to obtain a 300-mesh mixed material;
[0060] (2) stirring and dispersing a silane coupling agent, anhydrous ethanol and 22 wt % ammonia water in a mass ratio of 0.5:8:10 to obtain a mixed solution, wherein the silane coupling agent is γ-aminopropyltriethoxysilane and tetramethoxysilane in a mass ratio of 2:3;
[0061] (3) Add the mixed material to the mixed liquid, stir and disperse at room temperature for 15 minutes, then add acetic acid to adjust the pH to 6, raise the temperature to 45°C, control the ultrasonic power to 100W, the ultrasonic frequency to 60kHz, ultrasonically disperse for 15 minutes, and dry to constant weight to obtain the desired thermal conductive filler.
[0062] In the present invention, the composite antibacterial agent is prepared by the following method:
[0063] (1) A 2 mg / mL graphene oxide dispersion (active ingredient content 96%), a 0.05 mg / mL chitosan quaternary ammonium salt solution (degree of substitution 90%) and d-limonene were mixed in a mass ratio of 5:3:0.04, and the ultrasonic power was controlled to 90 W and the ultrasonic frequency to 60 kHz, and the mixed solution was obtained by ultrasonic dispersion for 15 min;
[0064] (2) After ultrasonic dispersion for 5 min at an ultrasonic power of 90 W and an ultrasonic frequency of 60 kHz, epichlorohydrin (8% by weight of the total mass of the mixed solution) was added and ultrasonic dispersion was continued for 10 min to form a complex;
[0065] (3) Drying the above-mentioned composite to a constant weight to obtain a composite antibacterial agent.
[0066] Comparative Example 1
[0067] The present invention provides a method for preparing environmentally friendly thermally conductive plastic particles, which specifically comprises the following steps:
[0068] S1. Material preparation: weigh 40 parts of low-density polyethylene, 20 parts of polyphenylene sulfide, 1 part of maleic anhydride grafted polyethylene, 50 parts of thermal conductive filler, 3 parts of composite antibacterial agent, and 5 parts of industrial magnesium hydroxide by weight, and set aside;
[0069] S2, material mixing: low-density polyethylene, polyphenylene sulfide, maleic anhydride grafted polyethylene, and thermal conductive filler are added to a high-speed mixer with a rotation speed of 1500 rpm, and the mixture is rotated for 15 minutes to be fully stirred and mixed to obtain a first mixture; then, the composite antibacterial agent and industrial magnesium hydroxide are added to the first mixture, and the mixture is rotated again at a rotation speed of 4500 rpm for 30 minutes, and the mixture is fully stirred and mixed to obtain a second mixture for standby use;
[0070] S3, molding preparation: the second mixture prepared in step S2 is extruded by a twin-screw extruder with a screw length-to-diameter ratio of 15:1, a rotation speed of 400 rpm, and a temperature of 280° C., and granulated to prepare thermally conductive plastic particles.
[0071] In the present invention, the thermal conductive filler is prepared by the following method:
[0072] (1) Pretreatment of aluminum oxide and aluminum: Aluminum oxide and aluminum are mixed and ground in a mass ratio of 8:12, and sieved to obtain a 200-mesh mixed material;
[0073] (2) stirring and dispersing γ-aminopropyltriethoxysilane, anhydrous ethanol, and 22 wt % ammonia water in a mass ratio of 0.1:4:4 to obtain a mixed solution;
[0074] (3) Add the mixed material to the mixed liquid, stir and disperse at room temperature for 15 minutes, then add acetic acid to adjust the pH to 5, raise the temperature to 45°C, control the ultrasonic power to 100W, the ultrasonic frequency to 60kHz, ultrasonically disperse for 15 minutes, and dry to constant weight to obtain the desired thermal conductive filler.
[0075] In the present invention, the composite antibacterial agent is prepared by the following method:
[0076] (1) A 2 mg / mL graphene oxide dispersion (active ingredient content 96%), a 0.05 mg / mL chitosan quaternary ammonium salt solution (degree of substitution 90%) and d-limonene were mixed in a mass ratio of 3:2:0.03, and the ultrasonic power was controlled to 90 W and the ultrasonic frequency to 60 kHz, and the mixed solution was obtained by ultrasonic dispersion for 15 min;
[0077] (2) After ultrasonic dispersion for 5 min at an ultrasonic power of 90 W and an ultrasonic frequency of 60 kHz, epichlorohydrin (3% by weight of the total mass of the mixed solution) was added and ultrasonic dispersion was continued for 10 min to form a complex;
[0078] (3) Drying the above-mentioned composite to a constant weight to obtain a composite antibacterial agent.
[0079] Comparative Example 2
[0080] The present invention provides a method for preparing environmentally friendly thermally conductive plastic particles, which specifically comprises the following steps:
[0081] S1. Material preparation: weigh 40 parts of low-density polyethylene, 20 parts of polyphenylene sulfide, 1 part of maleic anhydride grafted polyethylene, 50 parts of thermal conductive filler, 3 parts of composite antibacterial agent, and 5 parts of industrial magnesium hydroxide by weight, and set aside;
[0082] S2, material mixing: low-density polyethylene, polyphenylene sulfide, maleic anhydride grafted polyethylene, and thermal conductive filler are added to a high-speed mixer with a rotation speed of 1500 rpm, and the mixture is rotated for 15 minutes to be fully stirred and mixed to obtain a first mixture; then, the composite antibacterial agent and industrial magnesium hydroxide are added to the first mixture, and the mixture is rotated again at a rotation speed of 4500 rpm for 30 minutes, and the mixture is fully stirred and mixed to obtain a second mixture for standby use;
[0083] S3, molding preparation: the second mixture prepared in step S2 is extruded by a twin-screw extruder with a screw length-to-diameter ratio of 15:1, a rotation speed of 400 rpm, and a temperature of 280° C., and granulated to prepare thermally conductive plastic particles.
[0084] In the present invention, the thermal conductive filler is prepared by the following method:
[0085] (1) Pretreatment of aluminum oxide and aluminum: Aluminum oxide and aluminum are mixed and ground in a mass ratio of 8:12, and sieved to obtain a 200-mesh mixed material;
[0086] (2) tetramethoxysilane, anhydrous ethanol and 22 wt % ammonia water were stirred and dispersed in a mass ratio of 0.1:4:4 to obtain a mixed solution;
[0087] (3) Add the mixed material to the mixed liquid, stir and disperse at room temperature for 15 minutes, then add acetic acid to adjust the pH to 5, raise the temperature to 45°C, control the ultrasonic power to 100W, the ultrasonic frequency to 60kHz, ultrasonically disperse for 15 minutes, and dry to constant weight to obtain the desired thermal conductive filler.
[0088] In the present invention, the composite antibacterial agent is prepared by the following method:
[0089] (1) A 2 mg / mL graphene oxide dispersion (active ingredient content 96%), a 0.05 mg / mL chitosan quaternary ammonium salt solution (degree of substitution 90%) and d-limonene were mixed in a mass ratio of 3:2:0.03, and the ultrasonic power was controlled to 90 W and the ultrasonic frequency to 60 kHz, and the mixed solution was obtained by ultrasonic dispersion for 15 min;
[0090] (2) After ultrasonic dispersion for 5 min at an ultrasonic power of 90 W and an ultrasonic frequency of 60 kHz, epichlorohydrin (3% by weight of the total mass of the mixed solution) was added and ultrasonic dispersion was continued for 10 min to form a complex;
[0091] (3) Drying the above-mentioned composite to a constant weight to obtain a composite antibacterial agent.
[0092] Comparative Example 3
[0093] The present invention provides a method for preparing environmentally friendly thermally conductive plastic particles, which specifically comprises the following steps:
[0094] S1. Material preparation: weigh 40 parts of low-density polyethylene, 20 parts of polyphenylene sulfide, 1 part of maleic anhydride grafted polyethylene, 50 parts of thermal conductive filler, 3 parts of composite antibacterial agent, and 5 parts of industrial magnesium hydroxide by weight, and set aside;
[0095] S2, material mixing: low-density polyethylene, polyphenylene sulfide, maleic anhydride grafted polyethylene, and thermal conductive filler are added to a high-speed mixer with a rotation speed of 1500 rpm, and the mixture is rotated for 15 minutes to be fully stirred and mixed to obtain a first mixture; then, the composite antibacterial agent and industrial magnesium hydroxide are added to the first mixture, and the mixture is rotated again at a rotation speed of 4500 rpm for 30 minutes, and the mixture is fully stirred and mixed to obtain a second mixture for standby use;
[0096] S3, molding preparation: the second mixture prepared in step S2 is extruded by a twin-screw extruder with a screw length-to-diameter ratio of 15:1, a rotation speed of 400 rpm, and a temperature of 280° C., and granulated to prepare thermally conductive plastic particles.
[0097] In the present invention, the thermal conductive filler is prepared by the following method:
[0098] (1) Pretreatment of aluminum oxide and aluminum: Aluminum oxide and aluminum are mixed and ground in a mass ratio of 8:12, and sieved to obtain a 200-mesh mixed material;
[0099] (2) stirring and dispersing a silane coupling agent, anhydrous ethanol and water in a mass ratio of 0.1:4:4 to obtain a mixed solution, wherein the silane coupling agent is γ-aminopropyltriethoxysilane and tetramethoxysilane in a mass ratio of 1:2;
[0100] (3) Add the mixed material to the mixed liquid, stir and disperse at room temperature for 15 minutes, then add acetic acid to adjust the pH to 5, raise the temperature to 45°C, control the ultrasonic power to 100W, the ultrasonic frequency to 60kHz, ultrasonically disperse for 15 minutes, and dry to constant weight to obtain the desired thermal conductive filler.
[0101] In the present invention, the composite antibacterial agent is prepared by the following method:
[0102] (1) A 2 mg / mL graphene oxide dispersion (active ingredient content 96%), a 0.05 mg / mL chitosan quaternary ammonium salt solution (degree of substitution 90%) and d-limonene were mixed in a mass ratio of 3:2:0.03, and the ultrasonic power was controlled to 90 W and the ultrasonic frequency to 60 kHz, and the mixed solution was obtained by ultrasonic dispersion for 15 min;
[0103] (2) After ultrasonic dispersion for 5 min at an ultrasonic power of 90 W and an ultrasonic frequency of 60 kHz, epichlorohydrin (3% by weight of the total mass of the mixed solution) was added and ultrasonic dispersion was continued for 10 min to form a complex;
[0104] (3) Drying the above-mentioned composite to a constant weight to obtain a composite antibacterial agent.
[0105] Comparative Example 4
[0106] The present invention provides a method for preparing environmentally friendly thermally conductive plastic particles, which specifically comprises the following steps:
[0107] S1. Material preparation: weigh 40 parts of low-density polyethylene, 20 parts of polyphenylene sulfide, 1 part of maleic anhydride grafted polyethylene, 50 parts of thermal conductive filler, 3 parts of composite antibacterial agent, and 5 parts of industrial magnesium hydroxide by weight, and set aside;
[0108] S2, material mixing: low-density polyethylene, polyphenylene sulfide, maleic anhydride grafted polyethylene, and thermal conductive filler are added to a high-speed mixer with a rotation speed of 1500 rpm, and the mixture is rotated for 15 minutes to be fully stirred and mixed to obtain a first mixture; then, the composite antibacterial agent and industrial magnesium hydroxide are added to the first mixture, and the mixture is rotated again at a rotation speed of 4500 rpm for 30 minutes, and the mixture is fully stirred and mixed to obtain a second mixture for standby use;
[0109] S3, molding preparation: the second mixture prepared in step S2 is extruded by a twin-screw extruder with a screw length-to-diameter ratio of 15:1, a rotation speed of 400 rpm, and a temperature of 280° C., and granulated to prepare thermally conductive plastic particles.
[0110] In the present invention, the thermal conductive filler is prepared by the following method:
[0111] (1) Pretreatment of aluminum oxide and aluminum: Aluminum oxide and aluminum are mixed and ground in a mass ratio of 8:12, and sieved to obtain a 200-mesh mixed material;
[0112] (2) stirring and dispersing a silane coupling agent, anhydrous ethanol and 22 wt% ammonia water in a mass ratio of 0.1:4:4 to obtain a mixed solution, wherein the silane coupling agent is γ-aminopropyltriethoxysilane and tetramethoxysilane in a mass ratio of 1:2;
[0113] (3) Add the mixed material to the mixed liquid, stir and disperse at room temperature for 15 minutes, then add acetic acid to adjust the pH to 5, raise the temperature to 45°C, control the ultrasonic power to 100W, the ultrasonic frequency to 60kHz, ultrasonically disperse for 15 minutes, and dry to constant weight to obtain the desired thermal conductive filler.
[0114] In the present invention, the composite antibacterial agent is prepared by the following method:
[0115] (1) A 2 mg / mL graphene oxide dispersion (effective ingredient content 96%), water and d-limonene were mixed in a mass ratio of 3:2:0.03, and the ultrasonic power was controlled to 90 W and the ultrasonic frequency to 60 kHz, and the ultrasonic dispersion was performed for 15 min to obtain a mixed solution;
[0116] (2) After ultrasonic dispersion for 5 min at an ultrasonic power of 90 W and an ultrasonic frequency of 60 kHz, epichlorohydrin (3% by weight of the total mass of the mixed solution) was added and ultrasonic dispersion was continued for 10 min to form a complex;
[0117] (3) Drying the above-mentioned composite to a constant weight to obtain a composite antibacterial agent.
[0118] Comparative Example 5
[0119] The present invention provides a method for preparing environmentally friendly thermally conductive plastic particles, which specifically comprises the following steps:
[0120] S1. Material preparation: weigh 40 parts of low-density polyethylene, 20 parts of polyphenylene sulfide, 1 part of maleic anhydride grafted polyethylene, 50 parts of thermal conductive filler, 3 parts of composite antibacterial agent, and 5 parts of industrial magnesium hydroxide by weight, and set aside;
[0121] S2, material mixing: low-density polyethylene, polyphenylene sulfide, maleic anhydride grafted polyethylene, and thermal conductive filler are added to a high-speed mixer with a rotation speed of 1500 rpm, and the mixture is rotated for 15 minutes to be fully stirred and mixed to obtain a first mixture; then, the composite antibacterial agent and industrial magnesium hydroxide are added to the first mixture, and the mixture is rotated again at a rotation speed of 4500 rpm for 30 minutes, and the mixture is fully stirred and mixed to obtain a second mixture for standby use;
[0122] S3, molding preparation: the second mixture prepared in step S2 is extruded by a twin-screw extruder with a screw length-to-diameter ratio of 15:1, a rotation speed of 400 rpm, and a temperature of 280° C., and granulated to prepare thermally conductive plastic particles.
[0123] In the present invention, the thermal conductive filler is prepared by the following method:
[0124] (1) Pretreatment of aluminum oxide and aluminum: Aluminum oxide and aluminum are mixed and ground in a mass ratio of 8:12, and sieved to obtain a 200-mesh mixed material;
[0125] (2) stirring and dispersing a silane coupling agent, anhydrous ethanol and 22 wt% ammonia water in a mass ratio of 0.1:4:4 to obtain a mixed solution, wherein the silane coupling agent is γ-aminopropyltriethoxysilane and tetramethoxysilane in a mass ratio of 1:2;
[0126] (3) Add the mixed material to the mixed liquid, stir and disperse at room temperature for 15 minutes, then add acetic acid to adjust the pH to 5, raise the temperature to 45°C, control the ultrasonic power to 100W, the ultrasonic frequency to 60kHz, ultrasonically disperse for 15 minutes, and dry to constant weight to obtain the desired thermal conductive filler.
[0127] In the present invention, the composite antibacterial agent is prepared by the following method:
[0128] (1) A graphene oxide dispersion with a concentration of 2 mg / mL (active ingredient content 96%) and a chitosan quaternary ammonium salt solution with a concentration of 0.05 mg / mL (degree of substitution 90%) were mixed with water in a mass ratio of 3:2:0.03, and the ultrasonic power was controlled to 90 W and the ultrasonic frequency to 60 kHz, and the ultrasonic dispersion was performed for 15 min to obtain a mixed solution;
[0129] (2) After ultrasonic dispersion for 5 min at an ultrasonic power of 90 W and an ultrasonic frequency of 60 kHz, epichlorohydrin (3% by weight of the total mass of the mixed solution) was added and ultrasonic dispersion was continued for 10 min to form a complex;
[0130] (3) Drying the above-mentioned composite to a constant weight to obtain a composite antibacterial agent.
[0131] Comparative Example 6
[0132] The present invention provides a method for preparing environmentally friendly thermally conductive plastic particles, which specifically comprises the following steps:
[0133] S1. Material preparation: weigh 40 parts of low-density polyethylene, 20 parts of polyphenylene sulfide, 1 part of maleic anhydride grafted polyethylene, 50 parts of thermal conductive filler, 3 parts of composite antibacterial agent, and 5 parts of industrial magnesium hydroxide by weight, and set aside;
[0134] S2, material mixing: low-density polyethylene, polyphenylene sulfide, maleic anhydride grafted polyethylene, and thermal conductive filler are added to a high-speed mixer with a rotation speed of 1500 rpm, and the mixture is rotated for 15 minutes to be fully stirred and mixed to obtain a first mixture; then, the composite antibacterial agent and industrial magnesium hydroxide are added to the first mixture, and the mixture is rotated again at a rotation speed of 4500 rpm for 30 minutes, and the mixture is fully stirred and mixed to obtain a second mixture for standby use;
[0135] S3, molding preparation: the second mixture prepared in step S2 is extruded by a twin-screw extruder with a screw length-to-diameter ratio of 15:1, a rotation speed of 400 rpm, and a temperature of 280° C., and granulated to prepare thermally conductive plastic particles.
[0136] In the present invention, the thermal conductive filler is prepared by the following method:
[0137] (1) Pretreatment of aluminum oxide and aluminum: Aluminum oxide and aluminum are mixed and ground in a mass ratio of 8:12, and sieved to obtain a 200-mesh mixed material;
[0138] (2) stirring and dispersing a silane coupling agent, anhydrous ethanol and 22 wt% ammonia water in a mass ratio of 0.1:4:4 to obtain a mixed solution, wherein the silane coupling agent is γ-aminopropyltriethoxysilane and tetramethoxysilane in a mass ratio of 1:2;
[0139] (3) Add the mixed material to the mixed liquid, stir and disperse at room temperature for 15 minutes, then add acetic acid to adjust the pH to 5, raise the temperature to 45°C, control the ultrasonic power to 100W, the ultrasonic frequency to 60kHz, ultrasonically disperse for 15 minutes, and dry to constant weight to obtain the desired thermal conductive filler.
[0140] In the present invention, the composite antibacterial agent is prepared by the following method:
[0141] (1) A 2 mg / mL graphene oxide dispersion (active ingredient content 96%), a 0.05 mg / mL chitosan quaternary ammonium salt solution (degree of substitution 90%) and d-limonene were mixed in a mass ratio of 3:2:0.03, and the ultrasonic power was controlled to 90 W and the ultrasonic frequency to 60 kHz, and the mixed solution was obtained by ultrasonic dispersion for 15 min;
[0142] (2) Drying the mixed solution to a constant weight to obtain a composite antibacterial agent.
[0143] Performance Testing
[0144] The comprehensive properties of the thermally conductive plastic particles prepared in Examples 1-3 of the present invention and Comparative Examples 1-6 were verified respectively, as follows:
[0145] Thermal conductivity test: Tested according to the flash method described in the national standard GB / T 22588-2008;
[0146] Tensile strength test: Tested in accordance with national standard GB / T 1040.2-2022;
[0147] Antibacterial rate test: Tested in accordance with Appendix A of national standard GB 21551.2-2010;
[0148] Mildew resistance level test: Tested in accordance with national standard GB / T 24128-2018;
[0149] Corrosion resistance test: Tested in accordance with national standard GB / T 33383-2016;
[0150] The test results are shown in Table 1.
[0151] Table 1 Thermal conductivity and antibacterial and antifungal results of plastic particles in Examples 1-3 and Comparative Examples 1-6
[0152]
[0153]
[0154] As can be seen from Table 1, through the data of Examples 1-3 and Comparative Examples 1-3, it can be seen that the combined use of γ-aminopropyltriethoxysilane and tetramethoxysilane as modification agents for thermally conductive fillers, due to the complementarity of the functional groups of γ-aminopropyltriethoxysilane and tetramethoxysilane, makes the interface bonding between the filler and the polymer more firmly, forming a stronger interface layer. This enhanced interface bonding helps to reduce the interface thermal resistance of the system, thereby further improving the thermal conductivity of the composite material, and helps to optimize the distribution state of the filler, so that it is more evenly and densely distributed in the polymer matrix, thereby improving the overall thermal conductivity of the composite material, significantly improving the thermal conductivity, tensile strength and tensile strength after aging of the material, and improving the corrosion resistance of the material. It can be seen from Examples 1-3 and Comparative Examples 4-6 that the synergistic effect between the combined use of graphene oxide dispersion, chitosan quaternary ammonium salt solution and D-limonene can enhance dispersibility, improve antibacterial properties, and improve biocompatibility through epichlorohydrin coupling, significantly improving the antibacterial rate and mildew resistance level of the material. The present invention not only improves the overall mechanical properties and processing properties of plastic particles, but also enhances the ability of the material to resist microbial invasion, expands the scope of use of the material, and extends the service life of the product.
[0155] The above embodiments are only preferred embodiments of the present invention and are not any formal or substantial limitations of the present invention. It should be pointed out that ordinary technicians in this technical field can make several improvements and supplements without departing from the present invention, and these improvements and supplements should also be regarded as protection of the present invention.
Claims
1. A method for preparing environmentally friendly thermally conductive plastic particles, characterized in that: The specific steps include: S1. Material preparation: weigh 40-60 parts of polyethylene, 20-30 parts of polyphenylene sulfide, 1-3 parts of compatibilizer, 50-65 parts of thermal conductive filler, 3-5 parts of composite antibacterial agent, and 5-10 parts of processing aid, by weight, and set aside; S2, material mixing: adding polyethylene, polyphenylene sulfide, compatibilizer, and thermal conductive filler into a high-speed mixer, stirring and mixing them thoroughly to obtain a first mixture; then adding a composite antibacterial agent and a processing aid to the first mixture, stirring and mixing them thoroughly again, to obtain a second mixture for standby use; S3, molding preparation: the second mixture prepared in step S2 is extruded by a twin-screw extruder and granulated to obtain thermally conductive plastic particles.
2. The method for preparing environmentally friendly thermally conductive plastic particles according to claim 1, characterized in that: In the step S1, the polyethylene is low-density polyethylene, and the mass ratio of polyethylene to polyphenylene sulfide is 2-2.5:
1.
3. The method for preparing environmentally friendly thermally conductive plastic particles according to claim 1, characterized in that: The thermally conductive filler in step S1 is prepared by the following method: (1) Pretreatment of aluminum oxide and aluminum: Aluminum oxide and aluminum are mixed and ground in a mass ratio of 8-12:12-20, and sieved to obtain a 200-300 mesh mixture; (2) stirring and dispersing a silane coupling agent, anhydrous ethanol and 22-30 wt % ammonia water in a mass ratio of 0.1-0.5:4-8:4-10 to obtain a mixed solution; (3) Add the mixed material to the mixed liquid, stir and disperse, then add acetic acid, adjust the pH to 5-6, heat to 45°C, disperse by ultrasonic, and dry to constant weight to obtain the desired thermal conductive filler.
4. The method for preparing environmentally friendly thermally conductive plastic particles according to claim 3, characterized in that: The silane coupling agent is γ-aminopropyltriethoxysilane and tetramethoxysilane in a mass ratio of 1-2:2-3.
5. The method for preparing environmentally friendly thermally conductive plastic particles according to claim 1, characterized in that: The composite antibacterial agent in step S1 is prepared by the following method: (1) mixing graphene oxide dispersion, chitosan quaternary ammonium salt solution and d-limonene in a mass ratio of 3-5:2-3:0.03-0.04, and ultrasonically dispersing to obtain a mixed solution; (2) During the ultrasonic dispersion process, epichlorohydrin is added in an amount of 3-8% of the total mass of the mixed solution, and ultrasonic dispersion is continued to form a complex; (3) Drying the above-mentioned composite to a constant weight to obtain a composite antibacterial agent.
6. The method for preparing environmentally friendly thermally conductive plastic particles according to claim 1, characterized in that: The processing aid in step S1 is one or more of a flame retardant, a lubricant, an antioxidant, and a toughening agent.
7. The method for preparing environmentally friendly thermally conductive plastic particles according to claim 1, characterized in that: In step S2, the first mixture is prepared by stirring at a speed of 1500-2000 rpm in a high-speed mixer for 15-20 minutes, and the second mixture is prepared by stirring at a speed of 4500-6500 rpm in a high-speed mixer for 30-40 minutes.
8. The method for preparing environmentally friendly thermally conductive plastic particles according to claim 1, characterized in that: In step S3, the temperature of the twin-screw extruder is 280-300° C., the aspect ratio of the screw is 15-20:1, and the rotation speed is 400-500 rpm.